Answers

  • qais
  • Content Quality
2016-03-25T19:24:14+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
3x - 4y = 1
and x- 2y +1 =0
⇒x = 2y -1
putting this value in first equation,
3(2y -1) -4y =1
⇒6y -3 -4y =1
⇒2y = 4
⇒y =2
so, x= 2×2 -1 = 3
0
so now say...am i wrong?
I think so
omg...but where Rutvi??
I didn't understood your reply
you can also cross check that answer, i mean , put x =3 and y =2
2016-03-25T19:29:15+05:30
X = 2y -1
putting this value in first equation,
therefore 3(2y -1) -4y =1
= 6y -3 -4y =1
= 2y = 4
= y =2
       so, x= 2×2 -1 = 4-1
        = 3 is the answer
0
i want to edit it
ok
can i give the solution in chat
ok